Draft Fourth Five Year Plan (1966-71) Part- I Union Territory of Pondicherry - Planning Commission (Planning Commission, 1966)
As a result of the first two Plans, certain economic overheads, which were lacking, compared to other States were created. The food output went up by about 10%. A sizeable area was brought under sugarcane to feed a sugar factory, set up in the Territory in the private sector. Irrigation which had been neglected was considerably established facilitating a diversified crop pattern. A number of small and medium industries were also established. Textile production went up from 137.5 lakh metres in 1955 to 434.6 lakh metres in 1960.
Union Territory of Pondicherry